Increased relative abundance of Alistipes and Sellimonas is related to stage 2 and 3 sleep duration - Sasaki, Hiroyuki; Masutomi, Hirofumi; Ishihara, Katsuyuki (Frontiers in Sleep, 2025)
Sleep is important for maintaining body homeostasis, and lack of sleep or poor sleep quality increases the risk of various diseases. In recent years, it has been shown that there is an interaction between the gut microbiota and brain function, known as the brain-gut interaction. Although several studies have examined the relationship between gut microbiota and sleep, most of them rely on subjective indicators, and there are few reports using objective sleep measurements. Therefore, the aim of this study was to clarify the relationship between gut microbiota and sleep using various statistical analysis methods based on data obtained from the database. First, we obtained data from the Sukoyaka Health Survey, and performed hierarchical clustering analysis of the electroencephalogram (EEG)-derived sleep parameters. We examined the intestinal bacteria that differed significantly among clusters, and the relationship between intestinal bacteria and EEG-derived sleep parameters using multiple regression analysis and causal search. Multiple regression analysis and causal search suggested a relationship between increased Sellimonas levels and increased non-rapid eye-movement (non-REM) sleep stage 2, and increased Alistipes levels and increased non-REM sleep stage 3. The results of the causal search indicated that Alistipes and Sellimonas may influence the duration of non-REM sleep stage.